A thalamo-preoptic pathway promotes social grooming in rodents - Keller, Dávid; Láng, Tamás; Cservenák, Melinda; Puska, Gina; Barna, János; Csillag, Veronika; Farkas, Imre; Zelena, Dóra; Dóra, Fanni; Schimmer, Stephanie; Barteczko, Lara; Usdin, Ted B.; et al. (Current biology, 2022)
Social touch is an essential component of communication. Little is known about the underlying pathways and mechanisms. Here, we discovered a novel neuronal pathway from the posterior intralaminar thalamic nucleus (PIL) to the medial preoptic area (MPOA) involved in the control of social grooming. We found that the neurons in the PIL and MPOA were naturally activated by physical contact between female rats and also by the chemogenetic stimulation of PIL neurons. The activity-dependent tagging of PIL neurons was performed in rats experiencing physical social contact. The chemogenetic activation of these neurons increased social grooming between familiar rats, as did the selective activation of the PIL-MPOA pathway. Neurons projecting from the PIL to the MPOA express the neuropeptide parathyroid hormone 2 (PTH2), and the central infusion of its receptor antagonist diminished social grooming. Finally, we showed a similarity in the anatomical organization of the PIL and the distribution of the PTH2 receptor in the MPOA between the rat and human brain. We propose that the discovered neuronal pathway facilitates physical contact with conspecifics.